Anthropology in the financial crisis - Hart, Keith; Ortiz, Horacio (Anthropology Today, 2008)
This editorial considers the opportunities opened up for anthropologists by the financial crisis of 2008. The chief of these is the exposure of cracks in the intellectual hegemony of free-market economics which contributed to an unnecessarily defensive posture on the part of most anthropologists during the period of neoliberal globalization. The authors claim that anthropology can bridge the gap between everyday life and the world at large by combining the study of ideas and social actions. We draw on Ortiz's research among financial professionals to show how working practices informed by economic liberalism can have extremely unequal consequences for the global distribution of resources. The perspectives of Mauss and Polanyi on political economy can help us to make sense of the current situation and to recommend a path forward beyond market fundamentalism. Their general ideas lend power to the concrete findings of field research. The mask of neoliberal ideology has been ripped from the politics of world economy. Anthropology's highest mission is to start from where people are and go with them wherever they take you. What better time to follow this imperative than when the model the world has been compelled to live by for three decades is in such disarray?
Anthropology
Keywords: finance; financial crisis

Karl Polanyi's Legacy - Hart, Keith (Development and Change, 2008)
Click on the article title to read more.
Anthropology; Development Studies
Keywords: biography

After the disaster - Hart, Keith (Anthropology Today, 2008)
Naomi Klein's The Shock Doctrine offers a weak analysis of ‘neoliberalism’ linked to a defeatist ideology. If we wish to move beyond the global economic crisis, we should borrow ideas from Mauss, Polanyi and Keynes; but the political level for an appropriate response is not obvious.
Anthropology
Keywords: KLEIN; Naomi; neoliberalism

Karl Polanyi and the antinomies of embeddedness - Gemici, Kurtuluş (Socio-Economic Review, 2008)
While Polanyi argues that all economies are embedded and enmeshed in social relations and institutions, he tends to see market economy as disembedded, which reveals a tension in his thought. The main motivation for this paper is to understand the origins of this tension. On the basis of a systematic formulation of Polanyi's work, it is argued that Polanyi employs embeddedness in a dual manner: (a) as a methodological principle akin to methodological holism, and (b) as a theoretical proposition on the changing place of economy in society. These two formulations of embeddedness contradict each other. After tracing out the origins of this contradiction, this paper concludes by considering the implications of this analysis for economic sociology. It is argued that embeddedness as a methodological principle is the only acceptable usage of the term. Yet, in this capacity, embeddedness falls short of economic sociology's goal of providing a theoretical alternative to neoclassical economics.
Sociology; Anthropology
Keywords: Austrian history of economic thought; cultural economics; economic anthropology; economic sociology; economic systems; embeddedness; evolutionary; historical; institutional; relation of economics to other disciplines